Flotation of Smithsonite From Quartz Using Pyrophyllite Nanoparticles as the Natural Non-toxic Collector - Pan, Gaochan; Zou, Dan; Wang, Zhen (Frontiers in Chemistry, 2021)
Using nanometer natural hydrophobic mineral as collector in flotation is arousing the enthusiasm of researchers to explore. In this paper the separation performance and mechanism of pyrophyllite nanoparticles (PNP) on smithsonite and quartz flotation system were investigated through the method of flotation, zeta potential, contact angle and scanning electron microscope (SEM)/energy disperse spectroscopy (EDS). The single mineral flotation results showed that the difference in the flotation recovery of smithsonite and quartz was all great for NaOL, DDA and PNP collector in acid pH range, among which the biggest is the PNP system. At pH 6 the optimal dosage of PNP was 1000 mg/L. Using PNP collector to separate the mixed minerals of smithsonite and quartz could obtain the optimal concentrate indexes: Zn grade 50.84% and Zn recovery 85.36%. According to the results of zeta potential measurements the PNP and quartz were negatively charged while the smithsonite surface was positively charged at pH 6, which provided the condition for the selectively adsorption of PNP with smithsonite through the different electrostatic forces. The selective adsorption of PNP in smithsonite/quartz flotation system was directly observed by the SEM/EDS detection. The hydrophobic PNP adsorbed on hydrophilic smithsonite surface and resulting it hydrophobic, while the quartz surface remained hydrophilic. This is the mechanism for using PNP to separate smithsonite and quartz.